TEACHERS’ TECHNIQUES IN TEACHING SPEAKING SKILL FOR X-GRADE STUDENTS AT SMA YPVDP BONTANG IN THE ACADEMIC YEAR 2022/2023 - Destari, Dina; Hadijah, Sitti; Afendi, Achmad Ruslan; Wijayanti, Dwi Wahyu; Deliyani, Adinda (Tolis Ilmiah : Jurnal Penelitian, 2023)
Speaking, one of the four skills in English is seen as the most essential skill for English learners to master. Most people’s success in learning can be seen by how well they can talk and communicate. Teachers must have techniques in place to support the learning process and achieve specific characteristics in the teaching and learning process. This research aims to discover the techniques used by English teachers in teaching speaking skills to eighth-grade students at SMA YPVDP Bontang in the academic year 2022-2023. The qualitative descriptive method was employed in this study. An English instructor at SMA YPVDP Bontang, who taught class X, was the focus of this investigation. Interviews and observation were used to gather data, which was subsequently analyzed utilizing interactive, and condensation data models—utilizing data triangulation for data validation. The researcher found that teacher use three techniques, namely role play, small group discussions, and debates, to teach speaking skills.